PREDICTORS OF WOMEN ACADEMICS' CAREER PROGRESSION: EVIDENCE FROM AUSTRALIA - Hadrian G. Djajadikerta; Terri Trireksani (Asian Academy of Management Journal, 2007)
The issue of glass ceiling, invisible barriers that limit the access of women to higher level occupations and positions, continues to be of concern. Prior studies in this topic have been mostly conducted based on two perspectives: systemic and personal. However, neither of these two perspectives have managed to completely explain the glass ceiling phenomena in organizations. This paper focuses on higher education institutions in Australia. Incorporating both of these perspectives, this paper investigates the factors that influence career progression of women academics in Australian universities.